2021
DOI: 10.1371/journal.pone.0256077
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integrated model for supervision for mental health and psychosocial support in humanitarian emergencies: A qualitative study

Abstract: Background Despite recent advances in the development and provision of mental health and psychosocial support (MHPSS) in humanitarian settings, inadequate supervision remains a significant barrier to successful implementation. The present study sought to incorporate broad stakeholder engagement as part of the first phase of development of a new Integrated Model for Supervision (IMS) for use within MHPSS and protection services in humanitarian emergencies. Methods Semi-structured interviews were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…The finding in relation to certain qualities of supervisors that are perceived as being largely inherent to certain personality types, and therefore needing to be screened for in prospective supervisors, is consistent with the findings of a previous study [ 17 ], which interviewed key informants about supervision of MHPSS. The study by Perera et al [ 17 ] suggested that individuals with certain personal attributes should be selected to take on supervisory roles, rather than the role simply falling to individuals on the basis of reaching a certain level of seniority. Based on these findings, the IMS will provide guidance on the types of personal qualities and attributes that it may be useful to screen for when appointing MHPSS supervisors and will provide some suggestions around how to do so.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding in relation to certain qualities of supervisors that are perceived as being largely inherent to certain personality types, and therefore needing to be screened for in prospective supervisors, is consistent with the findings of a previous study [ 17 ], which interviewed key informants about supervision of MHPSS. The study by Perera et al [ 17 ] suggested that individuals with certain personal attributes should be selected to take on supervisory roles, rather than the role simply falling to individuals on the basis of reaching a certain level of seniority. Based on these findings, the IMS will provide guidance on the types of personal qualities and attributes that it may be useful to screen for when appointing MHPSS supervisors and will provide some suggestions around how to do so.…”
Section: Discussionsupporting
confidence: 89%
“…Participants were invited to vote on the validity of the statements on a Likert response scale ranging from 1 (strongly disagree) to 5 (strongly agree), as well as to comment in support of their votes. The statements were developed through previous phases of research and consultations as part of the ongoing development of the IMS: these phases included (1) a desk review of literature relating to the supervision of MHPSS in humanitarian settings (McBride et al [ 15 ]), (2) a series of key informant interviews (Perera et al [ 17 ]) and (3) workshop discussions on best practice in supervision for MHPSS in humanitarian settings [ 12 ]. The statements were devised by the first author, consulting the cited documentation of the previous phases of consultation, with particular focus on identifying areas of disagreement or gaps in information from the process up to that point.…”
Section: Methodsmentioning
confidence: 99%
“…On the same line, the result supported by (Perera et. al .,2021 ) (2) who demonstrated that more than half of studied nurses had moderate level, less than one fifth of them had high level, and only 20% of nurses had low counterproductive work behavior. These results disagreed a with the study by Ali & Johl (2020) (4) who revealed that studied nurses more likely to react with counterproductive work behavior with a low level of political skills.…”
Section: Discussionmentioning
confidence: 95%
“…In supervision, a designated staff member help subordinates to learn to make the best use of knowledge and skills, and to develop their abilities to achieve organizational goals. It is continuous process in which the supervisor helps the staff member achieves the purposes (Perera et al, 2021) (2) .…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing focus on its supportive role, on the necessity of providing learning opportunities in task-shifted interventions, and innovation in the areas of telemedicine, remote supervision and app-based learning. Furthermore, a more recent systematic review highlighted the importance of common factors across different treatment manuals commonly employed in task-sharing (Pedersen et al ., 2020 ), while a qualitative study with supervisors highlighted similar challenges to ours in balancing managerial, ‘objective-focused’ and supportive aspects of supervision in humanitarian emergencies (Perera et al ., 2021 ). Compared to 2019, the focus now has shifted more towards MH practices in LRHS, rather than ‘adapting approaches from the West’, as was done in some ways by initially reviewing competency tools from high income contexts.…”
Section: Discussionmentioning
confidence: 99%